2020
DOI: 10.1021/acs.energyfuels.0c03424
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Ammonia Addition on the Laminar Burning Velocities of Methane, n-Heptane, and Iso-octane

Abstract: Adiabatic laminar burning velocities for methane, n-heptane, and iso-octane blended with ammonia were experimentally determined using the heat flux method. The flames were stabilized at atmospheric pressure and at an initial temperature of 338 K, over equivalence ratios ranging from 0.7 to 1.4 and ammonia blending fractions in the binary fuel mixtures from 0 to 90%. These experiments are essential for the development, validation, and optimization of chemical kinetic models, e.g., for the combustion of gasoline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 130 publications
2
5
0
Order By: Relevance
“…Here the LBV of ammonia/CH 4 blends showed good agreement with literature data while discrepancy to literature data was found in fuel-rich ammonia/n-heptane and ammonia/iso-octane mixtures. A similar finding to Wang et al [30] has been observed by Lavadera et al [32] in binary ammonia/alkane fuels, i.e., the correlation between LBV and ammonia mass fraction in fuel blends is independent of alkane type. Moreover, as common recognition the enhancement of alkanes on LBVs is attributed to higher adiabatic flame temperature.…”
Section: Laminar Burning Velocitysupporting
confidence: 87%
See 1 more Smart Citation
“…Here the LBV of ammonia/CH 4 blends showed good agreement with literature data while discrepancy to literature data was found in fuel-rich ammonia/n-heptane and ammonia/iso-octane mixtures. A similar finding to Wang et al [30] has been observed by Lavadera et al [32] in binary ammonia/alkane fuels, i.e., the correlation between LBV and ammonia mass fraction in fuel blends is independent of alkane type. Moreover, as common recognition the enhancement of alkanes on LBVs is attributed to higher adiabatic flame temperature.…”
Section: Laminar Burning Velocitysupporting
confidence: 87%
“…The ozone enhancement was found to be stronger in higher alkanes and the promotion effect of O 3 was found to be attributed to O radical enrichment through early-stage O 3 decomposition. Lavadera et al [32] reported LBV measurements on binary fuel of ammonia and higher alkanes, namely, n-heptane and isooctane applying HF method at 298 and 338 K under 1 bar and ϕ between 0.7 and 1.4. Here the LBV of ammonia/CH 4 blends showed good agreement with literature data while discrepancy to literature data was found in fuel-rich ammonia/n-heptane and ammonia/iso-octane mixtures.…”
Section: Laminar Burning Velocitymentioning
confidence: 99%
“…There are six papers on this topic. Lavadera et al experimentally and numerically explore the blending of n -heptane, iso-octane, and CH 4 flames with NH 3 , and an overall good agreement between the measurements and simulated results was observed for the laminar burning velocities over the equivalence ratio and ammonia fraction ranges investigated. Wang et al investigate the effects of gas preheating and N 2 dilution on soot formation in a series of laminar methane (CH 4 ), ethane (C 2 H 6 ), and propane (C 3 H 8 ) co-flow diffusion flames.…”
Section: Nh3/ch4mentioning
confidence: 85%
“…Restricting the analysis to S L , as a comprehensive parameter representative of characteristic chemical timescales, some consideration on the NH 3 ammonia utilization can be drawn up. As a relevant parameter to combustion application, ICE and gas turbines, the laminar flame speed (S L ) of NH 3 has been experimentally characterized over the years with respect to mixture equivalence ratio (φ) (Figure 3) (Zakaznov et al, 1978;Ronney and Wachman, 1985;Pfahl et al, 2000;Jabbour and Clodic, 2004;Takizawa et al, 2008;Li et al, 2014;Hayakawa et al, 2015;Han et al, 2019;Mei et al, 2019;Lhuillier et al, 2020a;Lubrano Lavadera et al, 2020).…”
Section: Nh 3 Chemical and Physical Propertiesmentioning
confidence: 99%
“…Common strategies to improve NH 3 oxidation properties rely on the use of fuel "enhancers," such as H 2 , CH 4 , syngas, and other conventional or e-fuels (Pfahl et al, 2000;Okafor et al, 2018;Han et al, 2019;Lubrano Lavadera et al, 2020;Wang et al, 2020;Wang et al, 2021;Ariemma et al, 2022), in compliance with energy production decarbonization strategies, or modifying the environmental atmosphere toward O 2 -enriched conditions. H 2 can also be produced directly through NH 3 partial catalysis (Li et al, 2014) techniques, prior to the injection in combustion systems.…”
Section: Nh 3 Chemical and Physical Propertiesmentioning
confidence: 99%